Effects of Flammulina velutipes polysaccharides on quality improvement of fermented milk and antihyperlipidemic on streptozotocin-induced mice - Xinling Song (Elsevier, 2021)
Flammulina velutipes polysaccharide (FVP) has become a focus of attention due to its extensive physiological activity, and the addition of polysaccharides to probiotic fermented milk is a hot research topic in functional dairy products in recent years. In the present work, the physicochemical property and bioactivities of fermented milk contained with FVP isolated from fruiting body were evaluated. Our results indicated that fermented milk contained with FVP had better qualities and sensory scores. Moreover, in vivo data manifested that fermented milk contained with FVP could ameliorate hyperglycemia against diabetes by reducing blood glucose and insulin levels, and regulating dyslipidemia and the disorder of glycometabolism via the PI3K/Akt signaling pathway. Taken together, the study demonstrated that fermented milk contained with F. velutipes polysaccharides might be bioactive compounds for diabetes prevention, providing the basic theory for developing novel fermented drinks.